1988
DOI: 10.1111/j.1532-5415.1988.tb01811.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls and Instability in the Elderly

Abstract: D r Rubenstein Falls and gait instability are among the most serious problems facing the aging populationa major cause of mortality, morbidity, immobility, and premature nursing home placement. Many etiologies and risk factors predispose to falls, each requiring an individualized diagnostic and therapeutic approach to minimize likelihood of fall recurrence. In this discussion, two elderly individuals with complex, but fairly typical, fall problems are presented. These are followed by discussions of the epidemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
2
7

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(135 citation statements)
references
References 65 publications
3
123
2
7
Order By: Relevance
“…These results contradict the studies of Gryfre et al 26 and Rubenstein et al 27 , which showed positive correlations between the strength of the knee extensor muscles,, balance and the functional capability of elderly people. Gür and Çakin 28 proposed an explanation for this contradiction using multiple evaluations of the muscular groups which activate and move the knee.…”
Section: Discussioncontrasting
confidence: 56%
“…These results contradict the studies of Gryfre et al 26 and Rubenstein et al 27 , which showed positive correlations between the strength of the knee extensor muscles,, balance and the functional capability of elderly people. Gür and Çakin 28 proposed an explanation for this contradiction using multiple evaluations of the muscular groups which activate and move the knee.…”
Section: Discussioncontrasting
confidence: 56%
“…Numerous studies have shown that with advancing age, there is an increasing incidence of falling [1][2][3][4]. In the age 65 and over population, for example, 35-40% of community dwelling, generally healthy elderly persons fall annually [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…In 1998, approximately 10,000 people over the age of 65 year died from fall-related injuries [30]. Specifically, 75% of deaths due to falls in the United States occur in 13% of the population aged 65 and over [4]. Physical injury is only part of the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have indicated that with advancing age there is an increasing incidence of fatal slip and fall injuries (Agnew & Suruda, 1993;Campbell, Reinken, Allan, & Martinez, 1981;Donald & Bulpitt, 1999;Murphy, 2000;Rubenstein et al, 1988). Falls are the leading cause of death resulting from injury among older adults (over age 75) and the second highest cause of accidental death for 45-to 75-year-olds (National Safety Council, 2002).…”
Section: Introductionmentioning
confidence: 99%